Etudes floristique et ethnobotanique des plantes médicinales de la ville de Kénitra (Maroc) - Salhi, Souad; Fadli, Mohamed; Zidane, Lahcen; Douira, Allal (Lazaroa, 2011)
The aim of this work is to determine the medicinal plants used traditionally by the population of Kenitra, a town located in northwest Morocco. Research into medicinal flora allowed us to obtain 62 species belonging to 34 families and 58 types. Additional information was collected for ethnobotanical investigation by means of a questionnaire. The results of this study showed that the most commonly used part of the plant is the foliage. Some remedies are prepared by decoction. Among the ailments treated, digestive problems were overall the most frequently mentioned.